Neural and sensory applications of intervention in improving technique at high speed and race pace - Sweetenham, B. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The question is: How can technique and efficiency be improved and sustained at race speed and race pace swimming after 4 years or more of inefficient technique and motor pathway/muscle memory practice? Quotes of influence which indicate the purpose of the contents of this presentation: "The vast majority of athletes and swimmers can be trained to be good to great endurance athletes and swimmers, however only a very small few are bom to be sprinters and/or breaststrokers" Unfortunately a significant percentage of these endurance athletes and swimmers( based on flawed capability and capacity) desire and dream to be splint or speed athletes and swimmers. This is in contrast to nearly all speed and sprint people who have absolutely no desire, aspiration or inspiration to be endurance athletes and swimmers. This separation is a winning point of difference in swimming for China and the USA where there remains a real focus on 200m up and 1500/800m down swimming, in addition to the speed programmes. Both these countries have coaches, athletes and programmes pursuing success in these events with real intent focused on the Olympic podium. THE CONFLICT AND CONFUSION OF HAVING ENDURANCE ATHLETES FOCUSED ON SPEED EVENTS CHALLENGES ACCURATE TECHNIQUE DEVELOPMENT. COMPROMISED TECHNIQUE DEVELOPMENT IS RESPONSIBLE FOR LIMITING MANY SENIOR ATHLETES IN ACHIEVING THEIR OPTIMAL PERFORMANCE. "Anyone can become a marathon runner; but you are born a sprinter''